Pengaruh gaya kepemimpinan struktur inisiasi, subjektif diagnostik, subjektif interaktif terhadap keadilan evaluasi - Riski Hernando; Eko Prasetyo; Rezi Abdurrahman (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2020)
Abstract: This study aims to examine the effect of initiation structure leadership on evaluation fairness. This study also examines the mediation of subjective diagnostic and subjective interactive on the relationship between initiation structure leadership and evaluation fairness. The population and sample this study use subordinates in service, merchandising and manufacturing business. Data were collected using a questionnaire with hand delivery system technique and processed using structural equation modeling with WarpPLS 3.0 software. The results of this study indicate that initiation structure leadership influences evaluation fairness. However, mediation variable do not support the hypotheses in this study.Keyword: Evaluation Fairness, Initiation Structure Leadership, Subjective Diagnostic, Subjective Interactive